FEATURES OF GOAL-SETTING OF PUBLIC-PRIVATE PARTNERSHIP PROJECTS - Anton N. Melyukhin (Наука Красноярья)
The public-private partnership mechanism brings together different organizations in the process of project implementation, the initial goals of which may not coincide, which reduces the possibility of achieving the maximum value of the project. Therefore, the strategic context of agreeing on the common goal of the partnership between the public and private sectors is fundamental to its viability. In this article, the authors describe the process of goal-setting for PPP projects and present a model for setting goals and negotiations in PPP projects. Authors consider that the agreement on a common goal should be achieved in the process of negotiations between the participants, taking into account the interests of each party and ensuring the necessary combination of private and public interests to justify the performance indicators of PPP.